Web-based information system design of Graveyard licensing Administration in Grogol Selatan sub-district - Faizah, Faizah; Ishak, Riswandi; Widyastuti, Handini (Sinkron : jurnal dan penelitian teknik informatika, 2023)
: The role of service is very important in the current era of globalization, especially in government agencies engaged in services which will be needed by the applicant or the community. With time constraints and the impact of the Covid pandemic which has closed access to direct communication, it will make it difficult for some applicants or the public to apply for permits. The purpose of this research is to build a website that helps the One Stop Integrated Service (PTSP), so that applicants can apply online as one of the government's main functions in efforts to fulfill applications in the field of licensing services. Governor Regulation No. 47 of 2017 concerning instructions for the Implementation of One Stop Integrated Services (PTSP) for submitting applications for the issuance of Graveyard Land Use Permits (IPTM). This research is based on the waterfall software development method and data collection techniques with the results of observing the Web-Based Information System of Graveyard Licensing Administration in Grogol Selatan Sub-District